Penerapan Dan Kualitas Layanan Coretax Terhadap Kepatuhan WPOP Hipmi Cabang Surabaya - Jayanti, Fitri Dwi; Sukiswo, Wahyu Helmy Dimayanti (Gorontalo State University, 2026)
Tax reporting compliance among individual taxpayers plays an essential role in sustaining government revenue. Nevertheless, the level of compliance among young entrepreneurs remains relatively low. To address this issue, the government introduced the Coretax Administration System (CTAS) as part of tax administration modernization aimed at enhancing efficiency and improving service quality, although its implementation still encounters several technical obstacles. This research aims to analyze the effect of CTAS implementation and service quality on the level of tax reporting compliance among young entrepreneurs in Surabaya. A quantitative approach was employed using a survey method involving 105 respondents, who were selected through purposive sampling. The data collected were processed using Partial Least Squares (PLS) with the assistance of SmartPLS 4.0 software. The results indicate that both the implementation of CTAS and the quality of services significantly and positively influence tax reporting compliance, with an R-square value of 0.911. Among the variables examined, CTAS implementation shows the strongest contribution to compliance. These results underline the importance of optimizing the system and enhancing service quality to encourage sustainable tax reporting compliance.